Low Doses of Resveratrol Protect Human Granulosa Cells from Induced-Oxidative Stress - Beatriz Moreira-Pinto; Lia Costa; Eduarda Felgueira; Bruno M. Fonseca; Irene Rebelo (MDPI AG, 2021)
Resveratrol is a phytoalexin present in plant-derived foods, including grape's skin, cocoa, and peanuts. Evidence suggests that it has beneficial effects on human health because of its antioxidant properties. However, there is limited knowledge about the part played by resveratrol in ovarian function. In this paper, the influence of resveratrol on granulosa cells (GC) was evaluated. In addition to being the main estradiol producers, GC are in direct contact with the oocyte, playing a fundamental role in its growth and development. The cell line COV434 and human granulosa cells (hGC), obtained from women undergoing assisted reproductive technology (ART), were used. GC were treated with resveratrol (0.001-20 μM) at different times (24-72 h). Low concentrations of this compound suggest a protective role, as they tend to reduce ROS/RNS formation after inducement of stress. On the contrary, high concentrations of resveratrol affect GC viability and steroidogenic function. As it may act as a direct modulator of GC oxidative balance, this work may help to clarify the impact of resveratrol on GC and the usefulness of this antioxidant as adjunct to infertility treatments.